Harnessing the Four Elements for Mental Health - Sarris, Jerome; de Manincor, Michael; Hargraves, Fiona; Tsonis, Jack (Frontiers in Psychiatry, 2019)
Humans are intimately connected to nature, and our physical and mental health is influenced strongly by our environment. The ‘elements’, classically described in humoral theory as Fire, Water, Earth, and Air, all may impact our mental health. In a contemporary sense, these elements reflect a range of modifiable factors: UV light or heat therapy (Fire); sauna, balneotherapy, hydrotherapy (Water); nature-based exposure therapy, and horticulture (Earth); oxygen-rich/clean air exposure and breathing techniques (Air). This theoretical scoping review paper details the emerging evidence for a range of these elements, covering epidemiological and interventional data, and provides information on how we can engage in ‘biophilic’ activities to harness their potential benefits. Interventional examples with emerging evidentiary support include ‘forest-bathing’, heat-therapy, sauna, light-therapy, greenspace exercise, horticulture, ‘clay’ art therapy activities, pranayamic yoga breathing exercises. Further robust research is however required to firmly validate many of these interventions, and to establish the integrated therapeutic applications of them for the benefit of specific mental health disorders.